A method for investigating the cellular response to cyclic tension or compression in three-dimensional culture. (December 2018) - Sarrafpour, Babak; Boughton, Philip; Farahani, Ramin M.; Cox, Stephen C.; Denyer, Gareth; Kelly, Elizabeth; Zoellner, Hans
Abstract: We have an interest in the cellular response to mechanical stimuli, and here describe an in-vitro method to examine the response of cells cultured in a three-dimensional matrix to mechanical compressive and tensile stress. Synthetic aliphatic polyester scaffolds coated with 45S5 bioactive glass were seeded with human dental follicular cells (HDFC), and attached to well inserts and magnetic endplates in six well palates. Scaffolds were subjected to either cyclic 10% tensile deformation, or 8% compression, at 1 Hz and 2 Hz respectively for 6, 24 or 48 h, by uniaxial motion of magnetically-coupled endplates. It was possible to isolate high quality mRNA from cells in these scaffolds, as demonstrated by high RNA integrity numbers scores, and ability to perform meaningful cRNA microarray analysis, in which 669 and 727 genes were consistently upregulated, and 662 and 518 genes down regulated at all times studied under tensile and compressive loading conditions respectively. MetaCore analysis revealed the most regulated gene ontogenies under both loading conditions to be for: cytoskeletal remodelling; cell adhesion-chemokines and adhesion; cytoskeleton remodelling-TGF WNT and cytoskeletal remodelling pathways. We believe the method here described will be of value for analysis of the cellular response to cyclic loading. Graphical abstract: Highlights: Description of an in-vitro method to examine the response of cells to cyclic mechanical compressive or tensile stress. Use of synthetic aliphatic polyester 3D scaffolds which were seeded with human dental follicular cells. High quality mRNA isolated from cells stimulated by this method, permitting meaningful cDNA microarray analysis.